ความชุกของภาวะวิตกกังวลในผู้ป่วยอัมพาตครึ่งซีกจากโรคหลอดเลือดสมองที่เข้ารับการทำกายภาพบำบัด ณ โรงพยาบาลจุฬาลงกรณ์ - ชุติมา หรุ่มเรืองวงษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The purpose of this study was to examine the prevalence of anxiety and associated factors of 85 stroke patients who come to attend physical rehabilitation programs at King Chulalongkorn Memorial Hospital. The instruments used comprised of demographic data, Thai version of Hospital Anxiety and Depression scale, The Barthel ADL index, The personal Resource Questionires. : PRQ part II. and psychiatric interview. The data were analyzed for descriptive statistic : percentage, mean, standard division, Chi-square test and stepwise multiple regression analysis by SPSS for Windows. The result of this study were as follows : Prevalence rate of study was 24.7% and found that there are 3 factors associated significantly with anxiety. These factors are duration of the illness more than 6 months, Bathel ADL index at the level severe dependence and total dependence, and low social support. They are associated significantly with anxiety at statistical level p<0.01. From Stepwise Multiple Regression Analysis showed that all 3 factors still statistically associated with anxiety at level p<0.01.